An Urban Hyperreality: The Impact of Urban Digital Twin on Citizens’ Perception of the City - Morteza Hemmati; Hamid Khalili (گردشگری فرهنگ)
Digital twin is one of the groundbreaking media innovations in the city domain, which allows us to plan for complicated urban challenges using modeling and a virtual depiction of the actual environment, which reflects the idea of a smart city. Most of the studies and real-world experience demonstrate that such a technology is within the scope of urban management organizations and aligns with notions of smart cities and urban sustainability. With regard to resources, this technology medium seems to have the potential to lend itself to shaping the urban environment through the generation of meaning and urban narratives. In light of this information, the study aims to understand if it is possible to influence citizens’ perceptions of the city through urban digital twin technology?. This qualitative research aims to establish a link between accepted assumptions and established concepts from earlier studies. For this purpose, this study draws from available literature to generate a new assumption using the inductive research approach. The research’s conclusions demonstrate that by replicating a physical counterpart and modeling the actual world, it is possible to display a hyperreality parallel to what is happening in reality, giving the user a unique virtual experience. Interestingly, this experience, which is associated with a physical counterpart, can serve as a mental background. As much as the digital twin will be able to create a new interpretation of the place in the user’s mind, this medium can affect the urban landscape or citizens’ perception of it by creating a hyperreality of the real environment.